Measurement of the Effects of Nutritional Education for Reducing Sodium Intakes and Increasing Potassium Intakes. - Tchasso, Serge Kénao; SOSSA, JÉRÔME CHARLES; Paraiso, Moussiliou; SOPOH, GHISLAIN E. (My University, 2023)
Background: The Togolese population, like those around the world, frequently consumes foods high in salt/sodium and low in potassium, thus exposing them to cardiovascular disease (CVD). Nutritional intervention can help reverse this consumption pattern and reduce related CVD morbidity and mortality. The objective of this study was to measure the effects of a nutrition education intervention on the consumption frequencies of foods rich in sodium and potassium. Methods: The study was a quasi-experimental beforeand-after study, conducted from 08 January to 16 April 2023. It involved 200 adults aged 25 - 64 years, randomly selected from two areas: an intervention area and a non-intervention area. Data were collected in two phases at 3-month intervals in both groups. The intervention consisted of nutrition education (awareness raising and cooking demonstrations) on reducing salt/sodium intake and increasing potassium-rich food intake. The kobocollect electronic questionnaire was administered to the respondents to collect data on the frequency of consumption of foods rich in sodium and potassium. Results: The median age of the respondents was 33 years old (30; 38) and 56% of the participants were women, 44% and 69% respectively in the control and intervention groups. Most participants lived in rural areas (51%), 52.4% and 49.5% in the control and intervention groups respectively. Overall, 4% (p < 0.0089) of individuals reduced their frequency of adding salt at mealtime from more than 3 times a week to less than 3 times, i.e., 5.6% in the intervention group and 1.7% in the control group. The proportion of individuals who consumed meals with green leafy vegetable sauces was reduced from more than 3 times a week to less than 3 times, i.e., 7.5% (p < 0.022), or 1% in the intervention group and 4% in the control group. Education level (0.23 [0.10 - 0.50]; p < 0.0001) and male gender (4 [2.06 - 6.35]; p < 0.0006) were associated with reduced salt addition at meals. The same trend was observed for increased consumption of green leafy vegetable sauces (0.95 [0.03 - 0.99]; p < 0.011), male (2 [1.08 - 1.84]; p < 0.000) and other foods which were not significantly associated. Conclusion: This study was able to measure the effects of a nutrition education intervention for adequate sodium and potassium intakes on changing favourable dietary behaviour through a quasi-experimental study. The results show that the continuation of the intervention will contribute to the adoption of favourable behaviours for the reduction of dietary sodium intakes and the optimisation of potassium intakes.
Keywords: Nutrition Education; Consumption Frequency; Sodium/Salt; Potassium; Togo